The Megha-Tropiques mission: a review after three years in orbit - Roca, Rémy; Brogniez, Hélène; Chambon, Philippe; Chomette, Olivier; Cloché, Sophie; Gosset, Marielle E.; Mahfouf, Jean-Francois; Raberanto, Patrick; Viltard, Nicolas (Frontiers in Earth Science, 2015)
The Megha-Tropiques mission is operating a suite of payloads dedicated to the documentation of the water and energy cycles in the intertropical region in a low inclination orbit. The satellite was launched in October, 2011 and we here review the scientific activity after the first 3 years of the mission. The microwave sounder (SAPHIR) and the broad band radiometer (SCARAB) are functioning nominally and exhibit instrumental performances well within the original specifications. The microwave imager, MADRAS, stopped acquisition of scientific data on January 26th, 2013 due to a mechanical failure. During its 16 months of operation, this radiometer experienced electrical issues making its usage difficult and delayed its validation. A suite of geophysical products has been retrieved from the Megha-Tropiques payloads, ranging from TOA radiative flux to water vapor profiles and instantaneous rain rates. Some of these geophysical products have been merged with geostationary data to provide, for instance, daily accumulation of rainfall all over the intertropical region. These products compare favorably with references from ground based or space-borne observation systems. The contribution of the mission unique orbit to its scientific objectives is investigated. Preliminary studies indicate a positive impact on both, humidity Numerical Weather Prediction forecasts thanks to the assimilation of SAPHIR Level 1 data, and on the rainfall estimation derived from the Global Precipitation Mission constellation. After a long commissioning phase, most of the data and the geophysical products suite are validated and readily available for further scientific investigation by the international community.